Dead wood characteristics influencing macrofungal diversity in Sg. Menyala Forest Reserve and Kenaboi Forest Reserve, Negeri Sembilan - Che Ismail, Atikah (2019)
Macrofungal has a significant role in the forest ecosystem by decomposing wood and organic matter. This study was done to examine the abundance and richness of macrofungal, type of substrate, wood position, size, and decay stages that was affected by macrofungal in Sg. Menyala Forest Reserve (HSSM) and Kenaboi Forest Reserve (HSK). Macrofungal identification using macrofungal identification guideline was used to identify the macrofungal specimen. A several linear models and Two-sample Poisson test was used for statistical analysis. In this both study areas, there were 13 types of substrate namely branch, dead trunk, fallen dead tree, fallen leaves, buttress, fruit seed, living tree, soil, standing dead tree, stump, twig, wood debris and bamboo culm. Size, position and decay stage of dead wood are important factors to measure the macrofungal diversity. Size of dead wood was recorded according to three classes; Class 1 (dead wood with diameter size less than 2.5 cm), Class 2 (dead wood with diameter size between 2.5 cm to 15 cm) and Class 3 (dead wood with diameter size more than 15 cm). The position of dead wood occurred was recorded as vertical or horizontal position, while decay stage was recorded according to three stages; Stage 1 (fresh dead wood with the bark still intact), Stage 2 (dead wood with bark removed) and Stage 3 (dead wood almost completely decomposed). Both study areas show a highly significant difference of macrofungal abundance, morphospecies richness, and type of substrate. The results showed that the type of substrates affects the macrofungal abundance and composition. It can conclude that the efforts to conserve both forests are necessary since it provides the conducive environment for macrofungal diversity.